Optical Cavity Soliton and its Dynamics - Kaur, Baldeep (My University, 2017)
This thesis presents a theoretical study of generation and dynamics of cavity solitons in microcavities. We consider a wide area semiconductor cavity system that comprised of a vertical-cavity surface-emitting laser coupled with frequency-selective feedback. Three different cavity nonlinearities; cubic, cubic-quintic and saturating nonlinearities are considered. Cavity solitons are found in vertical-cavity surface-emitting laser with cubic and cubic-quintic nonlinearity by using variational method. The analytical cavity soliton solutions are validated by numerical split-step Fourier method. Spontaneous fission and subsequent generation of cavity soliton molecules, fusion and annihilation of cavity solitons are observed in the cavity with saturating absorber and frequency-selective feedback. The parametric space for generation of fronts, ∩-shaped and flat-top soliton solutions are identified. An alternate approach to generate cavity soliton is formulated by using standing wave method. This approach is shown capable for generation of a large variety of cavity solitons of different profile, ellipticity and power. A comprehensive stability analysis is done for different cavity soliton systems. Trivial and non-trivial homogeneous steady states of cavity soliton are obtained. Stable, Hopf instable and unstable regions of cavity solitons are marked. Using Lyapunov exponents method in conjugation with Hurwitz's criteria the stability regions are identified for both one and two dimensional cavity solitons. The skill of stability analysis is successfully extended to beyond optics. Stable zones for mechanical and biological systems are identified. The dynamics of cavity soliton is studied extensively to identify the effect of system parameters, such as, feedback strength, saturation, resonant frequency and amplitude on the dynamics as well as to explore novel phenomena. An intriguing all-optical ‘push-broom’ effect is demonstrated. The control on ‘push-broom’ effect by tuning system parameters is shown. The generated cavity soliton has potential application in all-optical selectively erasable memory and data processing. The wide stability regions identified in this thesis may be of significant benefit to the experimental observation of cavity soliton. The push broom may lead to a novel soliton force microscopy.
Ph. D. Thesis on theoretical Nonlinear Optics
Keywords: Cavity Soliton; dissipative soliton; stability analysis; complex Ginzburg-Landau equation; nonlinear dynamics; bifurcation